2019
DOI: 10.1002/jso.25578
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis in patients with synchronous colorectal cancer metastases after complete resection of the primary tumor and the metastases

Abstract: Background Synchronous metastases are considered a negative prognostic factor in patients with metastatic colorectal cancer (CRC). We investigated the outcomes of stage IV CRC patients undergoing complete gross resection (R0/1) of both the primary tumor and the metastases under the guidance of a multidisciplinary team (MDT). Methods All CRC patients with synchronous metastases were retrieved from a prospective database. Patients treated from 2006 to 2017 who underwent complete resection were analyzed. Various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 41 publications
1
15
1
Order By: Relevance
“…A significant difference in the median overall survival was observed at 10–11 months in those who underwent cancer‐directed surgery compared with 2–3 months in those who did not 19,20 . Furthermore, several studies performed in Europe have also shown a clear benefit in the survival of patients who undergo resection of both primary tumor and metastatic disease compared to those who did not 21‐23 . Siebenhuner et al (2020) performed a recent SEER review evaluating adult patients with diagnosis of metastatic colorectal cancer from 2010–2015 who underwent resection of primary tumor and metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…A significant difference in the median overall survival was observed at 10–11 months in those who underwent cancer‐directed surgery compared with 2–3 months in those who did not 19,20 . Furthermore, several studies performed in Europe have also shown a clear benefit in the survival of patients who undergo resection of both primary tumor and metastatic disease compared to those who did not 21‐23 . Siebenhuner et al (2020) performed a recent SEER review evaluating adult patients with diagnosis of metastatic colorectal cancer from 2010–2015 who underwent resection of primary tumor and metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…The median survival time of patients with unresectable intrahepatic metastases is less than 12 mo[ 20 ]. For patients with resectable CLM, the 5-year survival rate of those who choose radical resection is between 38% and 58%[ 21 , 22 ], and the benefits are obvious. We found that the following three factors determined the possibility of radical resection: The distribution of CLMs, the diameter of the largest CLM, and the distance to great vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Shimizu et al (80) recently analyzed the outcomes of PM in patients with a history of liver metastases and showed that a high preoperative CEA level was an independent prognostic factor for the overall survival. Although there have been only a few reports on PM for patients with both pulmonary and hepatic metastases detected simultaneously with the primary tumor, PM for such patients was still shown to provide favorable long-term outcomes (81,82). However, a history of distant metastases other than to the liver is believed to be a poor prognostic factor (72,79).…”
Section: Prognostic Factors For Each Tumor Type Crcmentioning
confidence: 99%